1981
DOI: 10.1111/j.1365-3083.1981.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Interaction between Entamoeba histolytica and Components of the Immune Response

Abstract: Binding to the surface of living E. histolytica trophozoites of 125I-labelled anti-amoeba antibodies or of such antibodies and antiglobulin resulted in a rapid disappearance of the antibody into the medium. This disappearance consisted of a rapid temperature-independent and a subsequent slow temperature-dependent phase. The disappearance of antibody from fixed trophozoites merely consisted of a temperature-independent rapid phase whereas no slow phase was observed. The magnitude of the rapid phase of antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Systemic antibody against E. histolytica develops after invasive disease (3,4), but does not appear to protect against recurrences (5, 6). Calderon et al (7) and Aust-Kettis et al (8) have shown that amebae in vitro can aggregate, ingest, and shed attached specific antiamebic antibody while remaining viable, a process that may be protective for the parasite. Normal and immune sera have been shown to be amebicidal via the alternate and classical pathways of complement (9)(10)(11); however, Reed et al (12) reported that amebae isolated from patients with liver abscess were resistant to complementmediated lysis.…”
mentioning
confidence: 99%
“…Systemic antibody against E. histolytica develops after invasive disease (3,4), but does not appear to protect against recurrences (5, 6). Calderon et al (7) and Aust-Kettis et al (8) have shown that amebae in vitro can aggregate, ingest, and shed attached specific antiamebic antibody while remaining viable, a process that may be protective for the parasite. Normal and immune sera have been shown to be amebicidal via the alternate and classical pathways of complement (9)(10)(11); however, Reed et al (12) reported that amebae isolated from patients with liver abscess were resistant to complementmediated lysis.…”
mentioning
confidence: 99%
“…Similar results were observed with antibodies against Leishmania spp. (Doyle, Behin, Mauel & Rowe 1984), T. cruzi (Abelha, Azevedo & Teixeira 1981), T. lewisi (Cherian & Dusanic 1978) and E. histolytica (Aust‐Kettis & Sundqvist 1980). Russo, Grab, Lonsdale‐Eccles, Shaw & Williams (1994) further showed that monoclonal antibodies were also internalized in T. brucei even in the absence of antigen–MAb‐001 complex.…”
Section: Discussionmentioning
confidence: 99%